2022
DOI: 10.21037/atm-22-2247
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota analysis with next-generation 16S rDNA gene sequencing in recurrent common bile duct stones

Abstract: Background: Endoscopic retrograde cholangiopancreatography (ERCP) is the main remedy for gallstones, but the postoperative recurrence rate is high. Recent research has indicated that the biliary microbiome takes part in the pathogenesis of cholelithiasis. However, it is not yet known whether biliary microbiome dysbiosis is relevant to recurrent cholelithiasis.Methods: Thus, we investigated the bacterial communities of the biliary microbiomes of patients with recurrent common bile duct (CBD) stones and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The connection between decreased microbial diversity and gallstone disease has been emphasized by previous research [ 9 , 16 , 27 , 28 ], highlighting the need to consider an individual’s overall gut microbiota composition when assessing their risk of developing this condition. Patients with recurrent cholelithiasis may exhibit an imbalance in their bile microbial communities, potentially contributing to gallstone formation [ 15 ]. Bile microbial communities in patients with primary CBD stones appear to be more evenly distributed than those in patients with recurrent CBD stones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The connection between decreased microbial diversity and gallstone disease has been emphasized by previous research [ 9 , 16 , 27 , 28 ], highlighting the need to consider an individual’s overall gut microbiota composition when assessing their risk of developing this condition. Patients with recurrent cholelithiasis may exhibit an imbalance in their bile microbial communities, potentially contributing to gallstone formation [ 15 ]. Bile microbial communities in patients with primary CBD stones appear to be more evenly distributed than those in patients with recurrent CBD stones.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MPS has significantly broadened our knowledge of the biliary tract microbiome and its role in health and illness [ 6 , 9 , 13 ]. Various studies have employed metagenomic sequencing to illustrate variations in the metabolic profile, bacterial diversity, and physiological states of the microbial communities in the CBD for choledocholithiasis [ 6 , 14 , 15 ] and the gallbladder for cholecystolithiasis [ 16 , 17 ]. However, as far as we are aware, no research has compared metagenomic differences in bile microbial communities based on the gallstone’s location in patients with choledocholithiasis or cholecystolithiasis.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies have demonstrated that gut microbes, such as Desulfovibrionales, can influence the formation of cholesterol-type gallstones by regulating bile acid production and cholesterol secretion ( Hu et al, 2022 ). Furthermore, dysbiosis in the biliary microbiota has been associated with the recurrence of bile duct stones ( Tan et al, 2022 ). Specific components of the bile microbiome, such as Enterobacteriaceae, have also been linked to the development of CHL and gallbladder cancer ( Choe et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%